Associations of Humidity and Temperature With Cataracts Among Older Adults in China - Lv, Xiaoyang; Gao, Xiangyang; Hu, Kejia; Yao, Yao; Zeng, Yi; Chen, Huashuai (Frontiers in Public Health, 2022)
Background: The burden of cataracts was substantial in the current aging world. However, few epidemiological studies have examined the associations between climate and weather conditions and cataract in older populations. We aimed to investigate the associations of air relative humidity and temperature with cataracts in older adults in China. Methods: We used the cohort data from 2002, 2005, 2008, 2011, 2014, and 2018 waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS). A total of 62,595 Chinese older adults aged between 65 and 105 years were included in the analyses. City-level annual average air humidity and temperature during 2001 and 2017 (before the survey year) was used to measure population exposure. A cataract was self-reports based on the medical record or the doctor's diagnosis and 8,071 older adults had cataract. Covariates included socio-demographic, health status, lifestyles, and chronic conditions. We adopted the Generalized estimation equation (GEE) model to analyze the associations of relative humidity and temperature with cataracts. Results: Significant associations were observed between both annual average relative humidity and temperature with the prevalence of cataracts, independent of potential confounders. The odds ratios were 0.99 (95% CI: 0.98,0.99) and 1.04 (95%CI: 1.03,1.05), respectively. The associations were robust in stratified analyses by sex, residence, and education level; it was stronger among females, rural older adults, and illiterate older adults. Furthermore, we found a nonlinear J-shaped relationship between temperature and cataract prevalence. Conclusion: Our findings provide the evidence that heat climate and low relative humidity may be associated with cataracts in older adults.